2021
DOI: 10.3390/ijerph182211765
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pharmaceuticals and Endocrine Disrupting Compounds in Brazilian Water and the Risks They May Represent to Human Health

Abstract: The risks of pharmaceuticals and endocrine disrupting compounds (P&EDC) to the environment and human health are a current topic of interest. Hundreds of P&EDC may reach the environment, hence, there is a need to rank the level of concern of human exposure to these compounds. Thus, this work aimed at setting a priority list of P&EDC in Brazil, by studying their occurrence in raw and drinking water, calculating health guideline values (GV), and estimating the risks of population exposure to water int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 82 publications
0
4
2
Order By: Relevance
“…Also, the level 4-NP, up to 0.590 μg/L recorded in this study was comparable to that up to 0.51 μg/L reported by Colin et al [ 111 ]. The results reported for both the raw and tap water samples from Ghana in the current study are relatively lower than those reported by de Aquino et al [ 101 ] in Brazilian water.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Also, the level 4-NP, up to 0.590 μg/L recorded in this study was comparable to that up to 0.51 μg/L reported by Colin et al [ 111 ]. The results reported for both the raw and tap water samples from Ghana in the current study are relatively lower than those reported by de Aquino et al [ 101 ] in Brazilian water.…”
Section: Resultscontrasting
confidence: 95%
“…de Aquino et al 101] reported levels of 64.8 μg/L, 6.81 μg/L, and 4.39 μg/L for BPA, βE2, and EE2 respectively in Brazilian raw water, which were significantly higher than what were recorded in raw water for the current study. Again in Brazilian drinking water, de Aquino et al [ 101 ] reported levels of 2.50 μg/L, 0.620 μg/L and 2.82 μg/L for BPA, EE2 and 4-NP respectively, that were higher than the levels recorded in the current study. These suggested that raw water samples studied in Brazil were relatively highly contaminated by these PXCs than that from Ghana in the current study, which retrospectively reflects the difference in levels reported in drinking water samples from the two studies.…”
Section: Resultscontrasting
confidence: 86%
“…On the other hand, for organic contaminants, data analysis and comparison has been performed in different countries evidencing the necessity of establishing strategies to remediate water pollution (Figure 1). These strategies are urgent, based on the potential risk that these contaminants can have on human health [88][89][90]. Although there are currently certain reports, guidance values or standards that allow establishing criteria based on the presence of these contaminants and their potential toxic effect are needed [43,91].…”
Section: Presence Of Pollutants In Water: Impact On Human Health and ...mentioning
confidence: 99%
“…Currently, there is a lack of consensus or adequate evidence concerning safety limits required to prevent the adverse effects of these substances on the environment or human health. Consequently, pharmaceutical products, especially those with endocrine-disrupting characteristics like the hormones in contraceptives, have become a focal point of investigation [ 5 ]. Notably, 17α-estradiol (EE2) is a prominent estrogenic steroid capable of causing harmful effects (endocrine disruption) even at extremely low concentrations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%